2021
DOI: 10.3390/cancers13215303
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Bacteremia and Risk Factors of Post-Radiofrequency Ablation Fever for Patients with Hepato-Cellular Carcinoma

Abstract: Post-radiofrequency ablation (RFA) fever is a self-limited complication of RFA. The correlation between post-RFA fever and bacteremia and the risk factors associated with post-RFA fever have not been evaluated. Patients with newly diagnosed or recurrent hepatocellular carcinoma who underwent ultrasonography-guided RFA between April 2014 and February 2019 were retrospectively enrolled. Post-RFA fever was defined as any episode of body temperature >38.0 °C after RFA during hospitalization. A total of 272 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…Regarding development of fever after the procedure in the current study, there were 64 patients (64%) of the studied group who had fever; this disagrees with Chen et al, who recently reported that the frequency of post-RFA fever was 18.4% [12], while Siriwardana et al reported a 25.2% rate of fever after TACE [13]. The differences are mainly related to assessment after a single intervention by Chen et al and Siriwardana et al in comparison to many percutaneous ablation therapies in our study or may be due to different antiseptic measures followed peri-procedurally, although they were followed during our interventions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding development of fever after the procedure in the current study, there were 64 patients (64%) of the studied group who had fever; this disagrees with Chen et al, who recently reported that the frequency of post-RFA fever was 18.4% [12], while Siriwardana et al reported a 25.2% rate of fever after TACE [13]. The differences are mainly related to assessment after a single intervention by Chen et al and Siriwardana et al in comparison to many percutaneous ablation therapies in our study or may be due to different antiseptic measures followed peri-procedurally, although they were followed during our interventions.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding development of fever after the procedure in the current study, there were 64 patients (64%) of the studied group who had fever; this disagrees with Chen et al ., who recently reported that the frequency of post-RFA fever was 18.4% [ 12 ], while Siriwardana et al . reported a 25.2% rate of fever after TACE [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advantages of less trauma, faster recovery and lower hospitalization cost than conventional hepatectomy, thermal ablation has been a promising strategy for HCC. In our study of 1491 ablation sessions performed over six years, 15.7 % patients developed postoperative SIRS after thermal ablation of HCC, which is similar to the previous studies [ 10 , 19 ]. Previously our team demonstrated that thermal ablation is safe in terms of major complications related to this procedure [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Chen et al reported the clinical features of post-RFA fever. They found the independent factors associated with fever were younger age, low albumin, general anesthesia, tumor size, and tumor number [ 5 ]. Huh et al performed a metanalysis to investigate the accuracy of radiological features in diagnosing tumor viability [ 6 ].…”
mentioning
confidence: 99%